Pengaruh Citra Merek, Inovasi Produk, dan Kualitas Produk Terhadap Minat Beli Ulang Skincare The Originote (Studi Kasus Pada Mahasiswa Universitas Muhammadiyah Aceh) - Fakhirah Zharifah; Nara Pristiwa; Yuslaidar Yuslaidar (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2025)
This study aims to analyze the influence of brand image, product innovation, and product quality on repurchase intention for The Originote skincare products. The research employs a quantitative method with a purposive sampling approach, which is categorized as non-probability sampling. The study population consists of 96 undergraduate students from Muhammadiyah University of Aceh who served as respondents. Data were collected through questionnaires using a Likert scale and analyzed using multiple linear regression with the SPSS Statistics 25 program. The results indicate that partially, brand image has a positive and significant effect on repurchase intention. Product innovation also has a positive and significant effect on repurchase intention, as does product quality, which shows a positive and significant influence. Simultaneously, the three variables significantly affect repurchase intention for The Originote skincare products. The findings of this study provide valuable insights and implications for skincare companies to strengthen brand image, enhance innovation, and maintain product quality to foster consumer loyalty.